In Memoriam: Alija Kulenović (1951-2004) - Buško, Vesna (2004)
It happened on Sunday, 5th of December 2004, dreadfully. Whole psychological and academic community, whoever knew him was truly shocked. Professor, adviser, fellow, supervisor, colleague, the dearest friend, Alija Kulenović passed away, for good. We lost one of the greatest Croatian scholars in psychological science, one of the most creative and productive researchers and lecturers, an unusually vigorous thinker, a humanist, an exceptional personality… He had a wide variety of intellectual interests and social concerns. The topics of the national and international research projects carried out under his supervision or wherein he collaborated as a researcher speak of the breadth of his scientific interests. Here are the titles of several of them: “Measurement in theoretical and applied psychological issues” ; “The structure and development of abilities, personality, and socialization in educational process” ; “The construction and evaluation of test battery for personality assessment based on interactionist model” ; “Cognitive, personality, and motivational characteristics of female soldiers” ; “Profiles of reading audience” ; “Influence of work and working conditions on employees’ life, health, and working capacities” ; “Work importance study” ; “Psychosocial climate in penal institutions”.
ENG